Image Formation Algorithm for Asymmetric Bistatic SAR Systems With a Fixed Receiver - Zeng, Tao; Liu, Feifeng; Hu, Cheng; Long, Teng (IEEE transactions on geoscience and remote sensing, 2012)
This paper proposes a highly accurate bistatic range migration algorithm (RMA) for space-surface bistatic synthetic aperture radar (BiSAR) systems with asymmetric configurations when the transmitter moves along a rectilinear trajectory and the receiver stays at a fixed location. The main work here includes three aspects. First, by introducing a 2-D change of frequency variables, an analytical 2-D spectrum formula without any approximation was derived at the first time. Second, with the linearity approximation of the derived phase, a highly accurate bistatic RMA was proposed and guaranteed that the algorithm could be applied to focus the echo from a large target scene. Furthermore, the nonlinear phase of the linearity approximation was analyzed to avoid the defocus effect in the final BiSAR image. Both simulation and indoor experimental results are presented to validate our analysis.